PENGARUH DIGITALISASI TERHADAP KEPATUHAN DAN PENERAPAN HUKUM PAJAK DI INDONESIA: Pengaruh Digitalisasi Terhadap Kepatuhan dan Penerapan Hukum Pajak di Indonesia - Abdul Rosyid , Muhammad; Pangesti , Indri; Hasanah , Nur; Mastutik, Siti (Mendapo: Journal of Administrative Law, 2024)
This work is licensed under a Creative Commons Attribution 4.0 International License This research explores the impact of digitalization on taxpayer compliance and the application of tax law in Indonesia in the era of digital transformation. Involving a qualitative approach with a focus on literature study and document analysis, this research illustrates how digital initiatives, such as e-Filing and e-Billing, implemented by the Directorate General of Taxes, have accelerated the efficiency of tax administration and made it easier to fulfill tax obligations. Literature studies review the importance of tax awareness, service quality, and public knowledge of the tax system, while research results show that digitalization has the potential to increase tax compliance. Evaluation of Directorate General of Taxes strategy highlights increased tax revenue through e-Filing and e-Billing, however, data security challenges and digital access gaps remain a concern. In the context of tax law implementation, this research highlights the adaptation of regulations to technology, digital supervision efforts, and the potential risk of tax fraud. The implications of digitalization for fiscal justice, contemporary tax theory, and the contribution of big data in optimizing tax rates are also detailed. This research concludes that digitalization provides opportunities and challenges that require holistic attention to ensure a tax transformation that is fair, efficient and in line with the development of the digital economy in Indonesia. This research explores the impact of digitalization on taxpayer compliance and the application of tax law in Indonesia in the era of digital transformation. Involving a qualitative approach with a focus on literature study and document analysis, this study illustrates how digital initiatives, such as e-Filing and e-Billing, are implemented by the Directorate General of Taxes in increasing tax revenue and strengthening taxpayer compliance. In addition, this research highlights the importance of strengthening data security and addressing the digital access gap to ensure successful digital transformation in taxation.